KADAR FIBRINOGEN SEBAGAI FAKTOR PROGNOSTIK PASIEN PERDARAHAN INTRASEREBRAL SPONTAN - David Tandian; Muhammad Harisyah; Hanif Gordang Tobing; Samsul Ashari; Renindra Ananda Aman; Syaiful Ichwan; Mohamad Saekhu; Wismaji Sadewo; Affan Priyambodo; Setyo Widi Nugroho (NEURONA, 2018)
FIBRINOGEN VALUE AS PROGNOSTIC FACTOR IN SPONTANEOUS INTRACEREBRAL HEMORRHAGEABSTRACTIntroduction: Spontaneous intracerebral haemorrhage (SIH) refers as spontaneous bleeding in the brain paren- chyma due to injury of blood vessels. Thus causing tissue inflammatory and coagulation reaction, activating the release of fibrinogen. Fibrinogen, an active substrate of coagulation cascade, also considered as the most powerful indicator of acute inflammatory response in SIH. Elevated levels of fibrinogen may be the marker for the increasing degree of brain tissue damage.Aims: Determine the correlation of fibrinogen levels with outcomes of patients with SIH who went on operative procedures.Methods: The study was conducted in Dr. Cipto Mangunkusumo hospital and its affiliation hospitals from January until August 2017. Total sampling was conducted. Preoperative Glasgow Coma Scale (GCS), blood volume, preoperative and postoperative serum fibrinogen values, and modified Rankin Scale (mRS) data were obtained and analyzed using the Spearman correlation test.Results: Significant correlation were found between the preoperative and postoperative fibrinogen with mRS score. Positive correlation coefficients were shown in both parameters, whereas the increase of preoperative and postoperative fibrinogen would increase the mRS score.Discussion: Pre and postoperative fibrinogen value showed significant association with mRS score, thereby they could be considered as prognostic predictive factors. However, because of the limited number of subject of this study to fulfill the criteria of validity study, a future study with a larger scale should be carried out.Keyword: Fibrinogen, mRS, outcome, spontaneous intracerebral haemorrhageABSTRAKPendahuluan: Perdarahan intraserebral spontan (PISS) adalah perdarahan spontan pada parenkim otak akibat kerusakan pembuluh darah pada jaringan otak. Kerusakan tersebut menimbulkan reaksi inflamasi jaringan dan koagulasi yang mengaktivasi pelepasan fibrinogen. Fibrinogen merupakan substrat aktif kaskade koagulasi yang juga merupakan penanda paling kuat respons akut inflamasi pada PISS. Adanya peningkatan kadar fibrinogen dapat menggambarkan peningkatan derajat kerusakan jaringan otak.Tujuan: Mengetahui korelasi kadar fibrinogen dengan luaran pasien dengan PISS yang dilakukan tindakan operatif.Metode: Penelitian dilakukan di RSUPN Dr. Cipto Mangunkusumo dan rumah sakit jejaring pendidikan dalam periode Januari–Agustus 2017. Sampel diambil dengan total sampling, data yang diambil adalah, Glasgow Coma Scale (GCS) preoperasi, volume perdarahan, kadar fibrinogen serum preoperasi dan pascaoperasi, dan modified Rankin Scale(mRS), kemudian dianalisis dengan tes Spearman correlation.Hasil: Dari uji statistik didapatkan hasil bermakna antara fibrinogen preoperasi mau pun pascaoperasi dengan skor mRS. Koefisien korelasi, menunjukkan korelasi positif pada keduanya, dimana peningkatan fibrinogen preoperasi dan pascaoperasi akan meningkatkan skor mRS.Diskusi: Fibrinogen pre dan pascaoperasi sebagai faktor prediksi prognostik memiliki hubungan bermakna dengan skor mRS. Namun dengan jumlah sampel penelitian yang masih belum mencukupi untuk memenuhi kriteria validitas untuk dapat diajukan sebagai faktor yang bersifat pasti, diperlukan penelitian lebih lanjut dengan sampel yang lebih besar.Kata kunci: Fibrinogen, luaran, mRS, perdarahan intraserebral spontan